2021
DOI: 10.1002/agj2.20590
|View full text |Cite
|
Sign up to set email alerts
|

Diallel analysis for resistance to northern leaf blight in popcorn under contrasting nitrogen availability

Abstract: Nitrogen-use efficient and leaf-disease resistant corn (Zea mays L.) cultivars are important to reduce costs and increase sustainability in farming. Studies have shown that non-additive genes may enhance nutrient-use efficiency and disease resistance in corn crops. This work aimed to analyze the responses of popcorn hybrids to northern leaf blight (NLB) under contrasting nitrogen availability. We evaluated NLB incidence and severity in 28 diallel hybrids and their parental lines. Competition trials were set in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…In environments with adequate water and nutrient supply [15][16][17] and under water-deficit conditions [18,19] as well as P and N stress [10,20,21], additive genetic action prevails for grain popping expansion, while non-additive action has been the most important in the expression of grain yield under water stress [14,18,19]. These results are also consistent with studies conducted with biotic stressors [22][23][24][25][26].…”
Section: Introductionsupporting
confidence: 83%
“…In environments with adequate water and nutrient supply [15][16][17] and under water-deficit conditions [18,19] as well as P and N stress [10,20,21], additive genetic action prevails for grain popping expansion, while non-additive action has been the most important in the expression of grain yield under water stress [14,18,19]. These results are also consistent with studies conducted with biotic stressors [22][23][24][25][26].…”
Section: Introductionsupporting
confidence: 83%
“…Genetic effects controlling popcorn traits under well-watered conditions (Larish and Brewbaker, 1999 ; Pereira and Amaral Júnior, 2001 ; Silva et al, 2010 ; Jele et al, 2014 ; Dar et al, 2018 ; Coan et al, 2019 ; Schwantes et al, 2020 ), biotic stresses (Schwantes et al, 2017 ; Mafra et al, 2018 ; Amaral Júnior et al, 2019 ; Kurosawa et al, 2020 , 2021 ), and nutritional deficiencies (Gerhardt et al, 2019 ; Santos et al, 2019 , 2020 ) have revealed that the additive genetic action is prevalent for PE, whereas the non-additive action has been the most important for GY expression and its components. In addition, non-additive genetic effects were the most prevalent controlling GY under water limitations in tropical maize (Betrán et al, 2003 ).…”
Section: Introductionmentioning
confidence: 99%
“…Particularly for popcorn production, which generates an annual turnover of about 1 billion dollars in the USA, to date all improved seed planted in Brazil must be imported, due to its higher grain yield and popping expansion, which AT Amaral Jr et al has motivated the development of research at the State University of Northern Rio de Janeiro (UENF), whose focus is the development of productive cultivars, with high expansion capacity, resistant to the main pathogens and pests and with better use of P. Genotypes are being developed with tolerance or resistance to biotic stresses (Schwantes et al 2018, Schmitt et al 2019, Kurosawa et al 2021; to abiotic stresses, in particular drought (Lima et al 2021, to low nitrogen , Khan et al 2021, Khan et al 2022) and to low P availability (Gerhardt et al 2017). In addition, genome wide selection (GWS) in a recurrent intrapopulation selection program was used to accelerate the breeding of superior segregating generations (Mafra et al 2019, Albino-Schwantes et al 2020.…”
Section: Introductionmentioning
confidence: 99%